Desain Visual Typografy pada Busana Casual T-Shirts dan Budaya Pop - Annita Komariati Prihandayani (Pascasarjana ISBI Bandung, 2021)
Studies on the typography transformation has historically experienced a shift in meaning, function, value, and form. Starting from casual clothes that can only be used for everyday clothing to semi-formal ones. The casual dress emphasizes comfort and personal expression over the presentation and uniformity of one's dress, which includes jeans and t-shirts. To examine these problems, a qualitative descriptive method is applied with a historical approach related to pop culture in modern society. The literature and feld analysis by using Levi-Strauss theory can help fnding answers in surface structure research (Surface – Structure). It shows that, the typography in casual clothing has changed, according to fashion trends. While in the inner structure (Deep – Structure), typography which is related to meaning and value, has no changes.Keywords: Transformation, Popular Culture, Typography, Casual fashion